2018
DOI: 10.1101/313536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterogeneous Absorption of Antimicrobial Peptide LL37 inEscherichia coliCells Enhances Population Survivability

Abstract: Antimicrobial peptides (AMPs) are broad spectrum antibiotics that selectively target 14 bacteria. Here we investigate the activity of human AMP LL37 against Escherichia coli by integrating 15 quantitative, population and single-cell level experiments with theoretical modeling. Our data 16 indicate an unexpected, rapid absorption and retention of a large number of LL37 by E. coli cells 17 upon the inhibition of their growth, which increases the chance of survival for the rest of 18 population. Cultures with hig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The bacterial cells would like to 'sacrifice' their life to the biosorption and biomineralization of heavy metals, so that the toxicity can be reduced. The similar sacrificing protection has also been observed in other hazardous materials, e.g., antibiotics (Snoussi et al, 2018). Bacterial life cycle has multiple stages.…”
Section: Discussionsupporting
confidence: 67%
“…The bacterial cells would like to 'sacrifice' their life to the biosorption and biomineralization of heavy metals, so that the toxicity can be reduced. The similar sacrificing protection has also been observed in other hazardous materials, e.g., antibiotics (Snoussi et al, 2018). Bacterial life cycle has multiple stages.…”
Section: Discussionsupporting
confidence: 67%
“…In another study, using sub-MIC of LL-37 against E. coli , authors demonstrated emergence of non-growing and growing population. The non-growing population adsorbed the peptide, reducing free peptide concentration allowing the rest of the population to grow (44). Dead E. coli cells also have been shown to provide protection against LL37 (45).…”
Section: Resultsmentioning
confidence: 99%